Pregnancy Outcomes in Women with Crohn’s Disease: A Literature Review - Teper, Maria; Kubiś, Natalia Marianna; Perz , Wiktor; Korolchuk , Anhelina; Polus , Aleksander; Palacz , Bartosz; Wrona, Julia Anna; Gluzicka , Anna; Olczyk , Liwia; Piotrowski , Jędrzej (Journal of Education, Health and Sport, 2026)
Background Crohn’s disease (CD) is a chronic inflammatory bowel disease commonly diagnosed in women of reproductive age. While treatments have improved over the years, pregnancy in women with CD still presents certain challenges. Recent findings suggest a strong link between disease activity and pregnancy outcomes. Aim To summarize contemporary evidence on pregnancy in women with CD, focusing on pathophysiological and clinical considerations, maternal outcomes, fetal and neonatal outcomes, disease monitoring during pregnancy, and selected high-risk clinical scenarios. Material and Methods This narrative review included articles published between 2015 and 2025 on pregnancy outcomes in women with CD. Relevant publications were identified using keywords such as CD, IBD, pregnancy, maternal and neonatal outcomes, disease activity, and monitoring. The analysis drew on clinical guidelines, observational studies, and narrative reviews, with no formal systematic review or meta-analysis applied. Results Disease activity at conception and during pregnancy emerged as the strongest determinant of pregnancy outcomes. Active disease was linked to higher risks of exacerbation, preterm birth (PTB), impaired fetal growth, and complications. Pregnancies conceived in remission were more often stable, with outcomes resembling those of the general population. Improvements over time reflect better disease monitoring, therapy, and multidisciplinary management. Conclusions Pregnancy outcomes in women with CD are primarily influenced by disease activity, not the diagnosis itself. Preconception counseling, remission, and structured monitoring are essential for optimizing maternal and fetal outcomes.